SAS2 : a guide to collaborative inquiry and social engagement - Chevalier, Jacques M., 1949-; Buckles, Daniel, 1955- (New Delhi : SAGE, 2016)
This title offers a new approach to creating and using knowledge for the common good. Its purpose is to broaden and deepen the range of concepts, tools and transferable skills to support dialogue and democratic engagement in the sphere of knowledge.
Specialized.
Description based on online resource; title from home page (viewed on January 13, 2016).
Keywords: elektronické knihy; electronic books; Social sciences -- Research; Social sciences -- Research -- Methodology